Chronic effects of tributyltin on multiple biomarkers responses in juvenile common carp, Cyprinus carpio - Li, Zhi-Hua; Li, Ping; Shi, Ze-Chao (Environmental toxicology, 2016)
In this study, the chronic toxic effects of tributyltin (TBT), an antifouling paints commonly present in surface and ground water, on morphological indices, reactive oxygen species (ROS) generation, and ATPase activity and heat shock protein (Hsp) 70 protein in tissues (liver, gill, and white muscle) of common carp were investigated. Fish were exposed at sublethal concentrations of TBT (75 ng/L, 0.75 μg/L, and 7.5 μg/L) for 60 days. When compared with the control, there was significant lower condition factor in fish exposed at the higher concentration of TBT. ROS levels in three tissues increased significantly at higher TBT concentrations (0.75 and 7.5 μg/L). The hepatic antioxidant enzymes (total antioxidative capacity and superoxide dismutase) activities were induced at higher concentrations (0.75 μg/L) of TBT. When compared with the hepatic antioxidant enzymes activities in fish exposed to 0.75 μg/L of TBT, there was a decreasing trend in those exposed to TBT with a concentration of 7.5 μg/L. However, all the antioxidant enzymes activities were significantly inhibited in gill and muscle of fish exposed to higher TBT concentrations (0.75 and 7.5 μg/L). Moreover, there was significant lower Na-K-ATPase in three tissues after long-term exposure to higher concentration of TBT, but a significant higher Hsp70 protein levels was observed. In short, environmental concentrations of TBT could not induce obvious impacts on fish, but long-term exposure to higher concentrations of TBT could affect seriously the health status of fish. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 937-944, 2016.
Keywords: Liver; Animals; proteiny tepelného šoku HSP70; orgánová specificita; Superoxide Dismutase; Sodium-Potassium-Exchanging ATPase; Antioxidants; Gills; biologické markery; játra; chemické látky znečišťující vodu; Biomarkers; superoxiddismutasa; Water Pollutants, Chemical; kapři; žábry; trialkylcínové sloučeniny; rybí proteiny; HSP70 Heat-Shock Proteins; antioxidancia; Trialkyltin Compounds; Fish Proteins; Carps; Organ Specificity; zvířata; sodíko-draslíková ATPasa